The diagnosis of diabetes mellitus based on HbA1C test from May to August 2017 - Ismail, Mohamad Anwar Syafiq (2017)
The measurement of the concentration of hemoglobin A1C or known as glycated hemoglobin in human bodies had been determined a new method by using the ion-exchange high-performance liquid chromatography (HPLC) principal that very sensitive for early detection of diabetes mellitus. Normal red blood cells in human body only survives for 8-12 weeks before renewal in erythropoiesis process, and by measuring the HbAlC concentration can reflect the average of blood glucose levels over that duration. This finding could replace the previous test such as fasting plasma glucose which the advantage of using the HbAlC test to measure glucose level in the blood rather than plasma glucose is that HbAlC test will give overall picture of glucose exposure over several months and the patient are not require to do fasting blood sugar. Moreover, HbAlC can minimize pre-analytical variability caused it is very stable after collection and produce no change in its concentration when transferred into the EDTA collection tube. Nowadays, the automation such as Biorad D-10 was worldwide used in the hospitals caused of their ability to produce result quickly. Based on other researches, the most common be suspected with diabetes disorder was high in women than men patients and the patients that 50 - 70 years old were the most affected with the high glycaemic exposure in their bodies.